The Association between the Social Vulnerability Index and Adverse Neonatal Outcomes - McCarley, Charlotte B.; Blanchard, Christina T.; Nassel, Ariann; Champion, Macie L.; Battarbee, Ashley N.; Subramaniam, Akila (American Journal of Perinatology, 2024)
Objective Identifying underlying social risk factors for neonatal intensive care unit (NICU) admission is important for designing interventions to reduce adverse outcomes. We aimed to determine whether a patient's exposure to community-level stressors as measured by the social vulnerability index (SVI) is associated with NICU admission.Study Design Retrospective cohort study (2014–2018) of patients delivering a liveborn ≥ 22 weeks' gestation at a quaternary care center. Patient addresses were used to assign each individual a composite SVI and theme score. The primary exposure was a composite SVI score categorized into tertiles. The primary outcome was NICU admission. Secondary outcomes included NICU length of stay and neonatal morbidity composite. Multivariable logistic regression was performed to estimate the association between composite SVI and outcomes (low SVI as referent). We secondarily compared mean composite and theme SVI scores; individual components of each theme were also compared.Results From 2014 to 2018, 13,757 patients were included; 2,837 (21%) had a neonate with NICU admission. Patients with higher SVI were more likely to self-identify as Black race and have medical comorbidities. Living in areas with moderate or high SVI was not associated with NICU admission (moderate SVI adjusted odds ratio [aOR]: 1.13, 95% confidence interval [CI]: 0.96–1.34; high SVI aOR: 1.12, 95% CI: 0.95–1.33). Moderate SVI was associated with increased neonatal morbidity (aOR: 1.18, 95% CI: 1.001–1.38). In an analysis of SVI as a continuous variable, mean SVI scores were significantly higher in individuals who had an infant admitted to the NICU. Those requiring NICU admission lived in areas with lower per capita income and a higher number of mobile homes (p < 0.001).Conclusion Patients living in areas with moderate or high SVI were not shown to have higher odds of having a neonate admitted to the NICU. Neonatal morbidity was higher in those living in areas with moderate SVI. Increased access to social services may improve neonatal outcomes.Key Points
Keywords: health disparities; perinatal; social determinants of health; social vulnerability; obstetric; maternal care